2020
DOI: 10.3390/info11080390
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Drivers’ Physiological Response to Different Vehicle Controllers in Highly Automated Driving (HAD): Opportunities for Establishing Real-Time Values of Driver Discomfort

Abstract: This study investigated how driver discomfort was influenced by different types of automated vehicle (AV) controllers, compared to manual driving, and whether this response changed in different road environments, using heart-rate variability (HRV) and electrodermal activity (EDA). A total of 24 drivers were subjected to manual driving and four AV controllers: two modelled to depict “human-like” driving behaviour, one conventional lane-keeping assist controller, and a replay of their own manual drive. Each driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The last paper "Measuring Drivers' Physiological Response to Different Vehicle Controllers in Highly Automated Driving (HAD): Opportunities for Establishing Real-Time Values of Driver Discomfort" by Radhakrishnan, Merat, Louw, Lenné, Romano, Paschalidis, Hajiseyedjavadi, Wei and Boer [21] investigates how driver discomfort was influenced by different types of automated vehicle (AV) controllers, compared to manual driving, and whether this response changed in different road environments, using heart-rate variability and electrodermal activity. The drivers were subjected to manual driving and four AV controllers: two modelled to depict "human-like" driving behavior, one conventional lane-keeping assist controller, and a replay of their own manual drive.…”
Section: Evaluating the Influence Of Driver State Driver Availabilitmentioning
confidence: 99%
“…The last paper "Measuring Drivers' Physiological Response to Different Vehicle Controllers in Highly Automated Driving (HAD): Opportunities for Establishing Real-Time Values of Driver Discomfort" by Radhakrishnan, Merat, Louw, Lenné, Romano, Paschalidis, Hajiseyedjavadi, Wei and Boer [21] investigates how driver discomfort was influenced by different types of automated vehicle (AV) controllers, compared to manual driving, and whether this response changed in different road environments, using heart-rate variability and electrodermal activity. The drivers were subjected to manual driving and four AV controllers: two modelled to depict "human-like" driving behavior, one conventional lane-keeping assist controller, and a replay of their own manual drive.…”
Section: Evaluating the Influence Of Driver State Driver Availabilitmentioning
confidence: 99%
“…Recent driving simulator experiments, using wearable electrodermal activity (EDA) and electrocardiogram (ECG) sensors, have shown a promising alternative to overcome eye-trackers major drawbacks and towards the development of multimodal DSM systems [34]- [37]. For example, simply detecting if the driver is taking a nap with the seat reclined, awake and listening to music while looking through the window, or fully immersed in a videogame may imply radically different preparation to take-over strategies to get the driver back in the loop.…”
Section: Introductionmentioning
confidence: 99%
“…Both ECG and EDA have proven their validity in detecting drivers' stress or mental workload in naturalistic driving [44] and driving simulators [37], [45], sleepiness [46], and discomfort [34]- [36]. In particular, increasing stress levels have been found under complex driving conditions [44], [47], possibly due to increased perceived risk.…”
Section: Introductionmentioning
confidence: 99%
“…Users' perception of an AV's driving style is known to be influenced by both objective and subjective factors. For example, road furniture and geometry are known to influence ratings of safety and comfort (Hajiseyedjavadi et al, submitted) and physiological response (Beggiato et al, 2019;Radhakrishnan et al, 2020), while a number of studies have shown a correlation between personality traits such as Sensation Seeking (Arnett, 1994) and preferred driving style. For example, in manual driving; drivers with high sensation seeking scores are found to drive in a riskier and more aggressive manner and at higher speeds, while low sensation seekers have higher tendency to drive more carefully (Louw et al, 2019;Taubman-Ben-Ari et al, 2004;Zuckerman & Neeb, 1980).…”
Section: Introductionmentioning
confidence: 99%